Spatial diversity of dung beetle assemblages (Coleoptera: Scarabaeinae) in five ecoregions from Sucre, Colombian Caribbean coast - Amell-Caez, Yina; Decastro-Arrazola, Indradatta; García, Héctor; Monroy-G, José D.; Noriega, Jorge Ari (Revista Colombiana de Entomología, 2019)
Biodiversity changes in space and time generate complex gradients. These gradients affect community structures, generating beta diversity replacement patterns. The two main patterns of spatial replacement are turnover and nestedness. However, there are very few studies that analyze diversity changes along environmental gradients in the Colombian Caribbean region. In an attempt to understand these spatial changes, a complete sampling was conducted in five Colombian Caribbean ecoregions (Golfo de Morrosquillo, Montes de María, Sabanas, San Jorge, and La Mojana) using dung beetles as an indicator. In each region, a linear transect with 20 pitfall traps baited with dung was established. Differences in abundance, richness, Shannon-index, evenness, and beta diversity between ecoregions were evaluated. A total of 923 individuals belonging to 27 species were collected. The tribe Deltochilini and the genus Canthon were the most diverse. The most abundant species was Silvicanthon aequinoctialis. Significant differences were found in the parameters measured between the ecoregions. A Beta diversity index established a clear spatial pattern demonstrating high turnover with low nestedness values. The Montes de María ecoregion has the highest diversity, which was linked with the maintenance of conserved forest fragments. It is advisable to generate conservation strategies and the designation of a new National Natural Park for Montes de María in order to stop the negative impact caused by agricultural and cattle farming expansion in the region. This study represents the first effort to understand dung beetle spatial patterns within the ecoregions of the Colombian Caribbean region through connecting environmental gradients and spatial diversity dynamics.